Adelaide Rosalia Hasse papers - Hasse, Adelaide Rosalia, 1868-1953.
Correspondence, subject files, printed matter, and other papers relating to Hasse's life and career as a bibliographer and librarian. Documents her development of the Superintendent of Documents Classification system used to classify and arrange government documents.
Librarian, bibliographer, and civil servant.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bibliographers; Bibliography; Classification -- Government publications; Librarians; Libraries; Superintendent of Documents Classification system; Bibliographers; Civil servants; Librarians